Construction technology for a shallow-buried underwater interchange tunnel with a large span. (November 2017) - Shi, Chenghua; Cao, Chengyong; Lei, Mingfeng
Abstract: The construction of underwater tunnels has become a major method for enabling transportation across rivers in cities. In this paper, several innovative ideas and methods adopted in the construction of the Yingpan Road Underwater Tunnel in Changsha, China were introduced. On the basis of the crossing function of traditional underwater tunnels, an underground interchange tunnel was designed, which could effectively overcome the bottleneck of regional transportation in cities and significantly expand the traffic function of tunnels. A method for determining the minimum burial depth of underwater tunnels was proposed by considering reinforcement control measures. This method indicated that the minimum burial depth of the Yingpan Road Tunnel was 11.5 m, which was shallower by over 5 m compared with existing data calculated using other methods. The tunnel length was also shorter by 400 m, which enhanced the traffic evacuation function of the tunnel. Seepage quantity in the tunnel during the service periods could be remarkably reduced by adjusting the thickness of the grouting reinforcement loop and the reinforcing parameters. By adopting advanced full-face pre-reinforcement and preliminary supports with double-layer steel and reasonably organising benching excavation, an ultra-shallow-buried large-section underwater tunnel with a depth/span ratio of only 0.46 and an excavation area of 376 m 2 was successfully excavated. The multi-operation and multi-section difficulties in constructing underwater super-large-section tunnels were overcome.